A65 VARIATION IN THE CARE OF CHILDREN WITH INFLAMMATORY BOWEL DISEASE: A CANGIEC POPULATION-BASED STUDY. (26th February 2020) - Kuenzig, E; Singh, H; Bitton, A; Kaplan, G G; Carroll, M W; Otley, A; Stukel, T A; Spruin, S; Griffiths, A; Mack, D; Jacobson, K; Nguyen, G C; et al.
Abstract: Background: Inflammatory bowel disease (IBD) is rising rapidly in Canadian children. These children require consistent high-quality specialized care to prevent long-term complications. Aims: Evaluate variation in health services utilization and surgery rates across pediatric IBD centres in Ontario. Methods: Incident cases of IBD <16y (1999–2010), identified from health administrative data using a validated algorithm, were assigned to pediatric IBD centres based on location of IBD hospitalization, endoscopy and outpatient care. Children receiving IBD-specific care outside pediatric centres were also grouped. Frailty models, median hazard ratios (MHR), and Kendall's t described variation in IBD-related ED visits, hospitalizations, and surgery 6–60 months after diagnosis, adjusting for age, sex, rural/urban household, and income. Mean diagnostic lag (time from first health system contact for an IBD symptom to final IBD diagnosis) and proportion of children with IBD care by gastroenterologists (GIs) at each centre were evaluated as centre-level predictors of variation. Results: Of 2584 IBD cases, 73.4% were treated in a pediatric IBD centre. Between-centre differences accounted for 0.18% (MHR 1.06) and 0.41% (MHR 1.09) of variation in hospitalizations and ED visits, respectively. Children treated at centres where a higher proportion of children were cared for by GIs were more likely to be hospitalized (HR 2.09, 95% CI 1.26–3.45). Children treated at centres with a longer mean diagnostic lag were also more likely to be hospitalized (HR 1.01, 95% CI 1.003–1.02). ED visits were not associated with the proportion of children cared for by gastroenterologists or diagnostic lag. Among 1529 CD cases, 14.1% required intestinal resection; 1.79% of variation in the risk of surgery resulted from between-centre differences (MHR 1.20). Surgery was less common among patients at centres where more children were cared for by GIs (HR 0.24, 95% CI 0.07–0.84) and with a longer mean diagnostic lag (HR 0.98, 95% CI 0.97–0.99). After adjusting for these, between-centre differences accounted for 0.005% (MHR 1.01) of variation in care. Minimal variation was observed among the 11.0% of 872 UC cases requiring colectomy, with 0.37% of variation due to between-centre differences (MOR 1.09). Colectomy risk was not associated with GI care or diagnostic lag. Conclusions: Variation in ED visits, hospitalizations, and surgery among children with IBD is small; however, centre-level differences in GI specialist care use and time to diagnosis were associated with hospitalization and surgery. It is essential to understand between-centre differences to reduce variation and ensure high-quality care. Funding Agencies: CCC